Comparación de los títulos de anticuerpos de la vacuna de newcastle administrado por el método de aspersión versus la vía oral en el agua de bebida en pollos broiler en la provincia de Tungurahua cantón Pelileo - Ramos Paredes, Enma Lizeth (2015)
This research was conducted in the Tungurahua province, Pelileo canton. The general objective was to compare antibody titles produced by the Newcastle vaccine administered by the method of spraying versus orally in the water in broiler chickens, and as specific objectives were: to determine which of the two methods of vaccination provides higher titles of antibodies to Newcastle disease, assessment of the rates of morbidity and mortality that occurs during the investigation and determine the cost benefit of using vaccination method sprinkler and orally in water in broiler chickens....